2015
DOI: 10.32607/20758251-2015-7-1-48-59
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PGC-1α Isoform Expression in Skeletal Muscles

Abstract: The coactivator PGC-1α is the key regulator of mitochondrial biogenesis in skeletal muscle. Skeletal muscle expresses several PGC-1α isoforms. This review covers the functional role of PGC-1α isoforms and the regulation of their exercise-associated expression in skeletal muscle. The patterns of PGC-1α mRNA expression may markedly differ at rest and after muscle activity. Different signaling pathways are activated by different physiological stimuli, which regulate the expression of the PGC-1α gene from the cano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 70 publications
2
36
0
Order By: Relevance
“…; Popov et al. 2015a). At rest, expression via the canonical promoter is high, while that via the alternative promoter is very low.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Popov et al. 2015a). At rest, expression via the canonical promoter is high, while that via the alternative promoter is very low.…”
Section: Introductionmentioning
confidence: 97%
“…Alternative promoters have the potential to play important roles in generating the complexity of human gene expression, in particular, in regulating gene expression via different promoter in a stimuli-specific manner. In rodent and human skeletal muscle, the PPARGC1A gene can be expressed via the canonical (proximal) and alternative (distal) promoters (Martinez-Redondo et al 2015;Popov et al 2015a). At rest, expression via the canonical promoter is high, while that via the alternative promoter is very low.…”
Section: Introductionmentioning
confidence: 99%
“…A key determinant of these endurance‐type adaptations is the transcriptional co‐activator, the peroxisome proliferator‐activated receptor‐γ co‐activator 1α (PGC‐1α). It has recently been shown that human muscle contains different PGC‐1α isoforms, and these isoforms may regulate different aspects of the muscle response to exercise . Furthermore, there is evidence for and against some of these isoforms (PGC‐1α1 and PGC‐1α4) responding to different types of exercise.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that human muscle contains different PGC-1a isoforms, 18 and these isoforms may regulate different aspects of the muscle response to exercise. 19 Furthermore, there is evidence for 18,20 and against 21,22 some of these isoforms (PGC-1a1 and PGC-1a4) responding to different types of exercise. But like the NKA isoforms, there is limited evidence about the effects of different ergogenic strategies on the regulation of the level of these isoforms in human muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that PGC‐1 α 4 expression may be promoted through β 2 adrenergic receptor signalling to the alternative promoter region (Popov et al . ). Pgc1α4 alternate splicing likely operates through small nuclear proteins assembling upon the pre‐mRNA substrate to excise intron sequences (House & Lynch ).…”
mentioning
confidence: 97%